Restoration and disintegration: the legacy of medical tradition in Plato's Philebus - Saar, Beatriz (Revista Archai, 2026)
This study aims to examine the position of medicine within the context of Plato's dialogue Philebus, focusing, on one hand, on the critique the philosopher makes of medicine as a practice and craft governed by specific norms and procedures, and, on the other, on the skillful way in which he draws upon certain medical theories, adapting them to serve his own purposes. The first part of the analysis seeks to understand the reasons behind Plato’s critique of medicine in the Philebus, especially in passage 56b1. This critique, as will be demonstrated, is closely related to the method of medicine. In this sense, it is important to highlight that, in criticizing medicine, Plato does not seek to establish a rivalry between philosophy and the medical practice, but rather to question medicine’s claim to sometimes present itself as the best and only modus vivendi. The second part of the study focuses on analyzing the influence of medicine on Plato’s theory of pleasure, particularly regarding the concept of pleasure as a process of fulfillment. To this end, Hippocratic texts such as On Diseases IV, On the Nature of Man, and On Ancient Medicine are consulted. Finally, through a comparison of recurring key terms, similarities and differences between the medical conception and Plato’s conception of pleasure are highlighted.